CompTIA A+ certification core 2 (220-1102). (Packt Publishing, 2022)
CompTIA offers certifications from basic IT fundamentals to A+ to networking, Linux, Cyber security, and more. The objectives of the CompTIA A+ Core 2(220-1102) are operating systems, security, software troubleshooting, and operational procedures. In this course, we will cover all four domains as per the latest exam syllabus. The first domain, Operating Systems, carries 31% of the exam and comprises operating system types and purposes (Windows, macOS, iOS, Android, Linux, and so on), Windows versions, OS installation, and command-line tools. The second domain, namely Security, holds 25% of the exam and consists of physical and logical security concepts, wireless security protocols, social engineering threats, attacks, and more. The third domain, which holds 22% of the exam, is Software Troubleshooting which explains how to troubleshoot Microsoft OS, PC security, mobile OS, and application issues as well as malware removal. The last and final domain of the exam is Operational Procedures, which holds 225 weightage and explains best practices for documentation, change management, disaster prevention and recovery, safety procedures, and more. It also includes different types of licenses and policies, professional conduct, remote access technologies, and so on. By the end of the course, we will make sure you are ready to pass the CompTIA A+ Core 2(220-1102) exam. What You Will Learn Explore different operating systems: Windows, Mac, Linux, iOS, Android Understand security concepts such as malware, anti-malware, and networking security protocols Learn to secure your computer, mobile device, and network Troubleshoot software and mobile issues Learn to use command-line tools in Windows, Mac, and Linux Explore the different types of operational procedures Audience This course is for anyone looking to take and pass the CompTIA A+ Certification Core 2 (220-1102) certification exam; anyone who wants to improve their skills as a computer or IT technician; and anyone who wants to learn awesome stuff about Windows, macOS, Linux, mobile, IT security, scripting, and more. A basic familiarity with computers and networks is helpful. Furthermore, CompTIA recommends having 9-12 months of on-the-job experience before taking the A+ exam. This is recommended but not required. About The Authors Mike Meyers: Total Seminars, LLC, is a provider of PC and network repair seminars and certification training services through books, videos, and courseware for thousands of organizations throughout the world including the United Nations, the FBI, and all branches of the US Department of Defense. Mike Meyers is the president and co-founder of Total Seminars, which produces the best-selling CompTIA A+ and Network+ Certification books with over 1 million books in print. He is affectionately called the "Alpha Geek" and is the industry's leading authority on CompTIA Certifications. He has created several other best-selling video courses on CompTIA certifications with the Total Seminars team of instructors. Mike has been involved in the computer and network repair industry since 1987 as a technician, instructor, author, consultant, and speaker. He is the author of numerous popular PC books and videos, including the best-selling CompTIA A+ Certification All-In-One Exam Guide and CompTIA Network+ Certification All-In-One Exam Guide. His humorous and easy-to-follow approach to teaching comes through in his video training courses as well as his classroom instructor-led courses. Making IT concepts easy to understand and fun to learn helps students stay engaged and retain the information. Steve Nicholson: Steve Nicholson is an information security professional with decades of experience in IT. Ever the problem-solver, Steve specializes in digital forensics and incident response, holding an MS in Digital Forensics from UCF, multiple GIAC certifications, and the coveted Lethal Forensicator title. A Marine Corps veteran, Steve volunteers time between both the Marine Corps Cyber Auxiliary and the Civil Air Patrol's CyberPatriot programs and sits on the FLDOE Cybersecurity Curriculum Committee. He is also the NSA program administrator for his college's Center of Academic Excellence in cyber defense. Having taught many students over the years, Steve's favorite part about educating people is the "AHA!" they have when learning something new or perfecting a difficult skill.